Comparison of Indian and Southern African fossil angiosperm woods - Bamford , Marlon (Rheedea, 1996)
The few fossil woods that have been described from southern Africa are compared, at generic level, to woods from India. They belong to fairly large families and, except for Xanthophyllum and Hedycarya, have a similar extant distribution. The southern African fossil woods show that a tropical and wet climate extended much farther south during the Miocene than it does today. Evolutionary changes in the wood structures have occurred at the species level. The picture is incomplete and continuing research may show some interesting trends.